WORKSHOP PENGENALAN APLIKASI PENDUKUNG PEMBELAJARAN BAGI GURU SD IT AR-RISALAH SAMARINDA - Achmad Maulana (COVIT (Community Service of Health), 2021)
Education is basically a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential. Technology is also a tool for the use of knowledge and science. Technology also enters various fields in human life to increase the effectiveness of a production or activity for its users. The world of education is also inseparable from the integration of technology in the context of learning effectiveness and efficiency. The use of technology as a learning medium has great benefits in making it easier for students to learn the subject matter. In order to increase the ability of SD IT Ar-Risalah Samarinda teachers in utilizing technology, there will be an introduction to learning support application training in schools. So that later they can maximize the delivery of a flow of learning information to students. The purpose of this activity is to utilize technology in classroom learning, including in creating a simple LMS (Learning Management System) that utilizes features in Google. From this community service activity, it can be concluded that, With the introduction of learning support applications, participants.